Functional Outcome and Safety of Intracranial Thrombectomy After Emergent Extracranial Stenting in Acute Ischemic Stroke Due to Tandem Occlusions - Bücke, Philipp; Aguilar Pérez, Marta; AlMatter, Muhammad; Hellstern, Victoria; Bäzner, Hansjörg; Henkes, Hans (Frontiers in Neurology, 2018)
Background and Purpose: Various endovascular approaches to treat acute ischemic stroke caused by extra- intracranial tandem occlusions (TO) exist: percutaneous transluminal angioplasty with or without emergent extracranial carotid stenting (ECS) due to high-grade stenosis preceded or followed by intracranial mechanical and/or aspiration thrombectomy (MT). Which treatment strategy to use is still a matter of debate. Methods: From our ongoing prospective stroke registry we retrospectively analyzed 1,071 patients with anterior circulation stroke getting endovascular treatment within 6 h of symptom onset. ECS prior to intracranial MT for TO (n = 222) was compared to MT as standard of care (control group; acute intracranial vessel occlusion without concomitant ipsilateral ICA-occlusion or high-grade stenosis [C; n = 849]). Good functional outcome (mRS ≤ 2 at 3 months), mortality rates, frequencies of symptomatic intracranial hemorrhage (sICH) and successful recanalization (Thrombolysis in Cerebral Infarction Score [TICI] 2b or 3) were assessed. In subgroup analyses we tried to detect possible influences of stroke etiology, dual inhibition of platelet aggregation (IPA; clopidogrel [CLO]: n = 83; ticagrelor [TIC]: n = 137; in combination with Aspirin) and intravenous thrombolysis (IVT). Results: Functional outcome was superior in TO (mRS 0–2: 44.6%) when compared with controls (36.0%; OR [95% CI]: 3.49 [1.59–7.67]; p = 0.002). There was no difference in all-cause mortality at 3 months (TO: 21.6%; C: 27.7%; 0.78 [0.47–1.29]; p = 0.324), in-hospital mortality (0.76 [0.45–1.30]; p = 0.324), sICH (TO: 3.2%; C: 5.0%; 0.70 [0.30–1.59]; p = 0.389), and TICI 2b/3 (TO: 89.1%; C: 88.3%; p = 0.813). In subgroup-analysis, TIC and CLO did not differ in functional outcome (TIC: 45.3%; CLO: 44.6%; 1.04 [0.51–2.09]; p = 0.920) and mortality rates (all-cause mortality: TIC: 23.4%; CLO: 16.9%; 0.75 [0.27–2.13]; p = 0.594). sICH was more frequent in TIC (n = 7 [5.1%]) vs. CLO (n = 0; p = 0.048). Conclusion: In our pre-selected cohort, ECS prior to intracranial MT in TO allowed for a good functional outcome that was superior compared to a control population. Mortality rates did not differ. Despite a dual IPA in TO, there was no increase in sICH. CLO and TIC for dual IPA did not differ in terms out outcome and mortality rates. A significant increase in sICH was observed after initial loading with TIC.